Optimizing multicast flows in high-bandwidth reconfigurable datacenter networks. (July 2022) - Luo, Long; Foerster, Klaus-Tycho; Schmid, Stefan; Yu, Hongfang
Abstract: Modern cloud applications has led to a huge increase in multicast flows, which is becoming one of the primary communication patterns in nowadays datacenter networks. Emerging datacenter technologies enable interesting new opportunities to support such multicast traffic more effectively and flexibly in the physical layer: novel circuit switches offer high-bandwidth and reconfigurable inter-rack multicasting capabilities. However, not much is known today about the algorithmic challenges introduced by this new technology, especially in optimizing the completion times for multicast flows. This paper presents SplitCast, a preemptive multicast scheduling approach that fully exploits emerging high-bandwidth physical-layer multicasting capabilities to reduce flow times. SplitCast dynamically reconfigures the circuit switches to adapt to the multicast traffic, accounting for reconfiguration delays. In particular, SplitCast relies on simple single-hop routing and leverages transfer flexibilities by supporting splittable multicast so that a transfer can already be delivered to just a subset of receivers when the circuit capacity is insufficient. Moreover, SplitCast supports two common forwarding models, the all-stop and the not-all-stop, during circuit reconfiguration. We conduct extensive simulation to evaluate the performance of SplitCast, and the results show that SplitCast can cut down flow times significantly compared to state-of-the-art solutions.